EFFECTIVENESS OF RED ROSE (Rosa damascena Mill) EXTRACT AS A ROOT CANAL STERILIZATION MATERIAL: EFEKTIVITAS EKSTRAK BUNGA MAWAR MERAH (Rosa Damascena Mill) SEBAGAI BAHAN STERILISASI SALURAN AKAR GIGI - Asri Riany; Bunga Isyadestia; Putu Rusmiany (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2022)
Introduction: Necrotic teeth can be preserved by root canal treatment. One of the important steps in root canal treatment is root canal sterilization. In recent years, many researchers have researched herbal ingredients to replace chemicals that have been widely used, because the side effects of these herbal ingredients are relatively low and the price is relatively cheaper. The purpose of this study was to determine the effectiveness of red roses in inhibiting the growth of tooth root canal bacteria. Materials and Methods: In this study, we investigated herbal ingredients, namely red rose flower extract (Rosa Damascena Mill) as antibacterial ingredients. This research is a laboratory research with Post Test Control Group Design. The samples used were root canal bacteria which were divided into 4 groups, namely: group 1 was the treatment group given 75% red rose extract, the second group was given 100% red rose extract, the third group was given positive control ChKM. and group 4 treatment group which was treated with aquadest negative control, with each repetition 4 times. Extraction of red roses was carried out by maceration method using 96% ethanol as solvent. Inhibition zone testing was carried out using the Kirby Baurer. Results: The calculation results obtained a significant value using the Kruskal-Wallis ChKM, 75% red rose extract, 100% red rose extract, and aquadest. Conclusion: Red rose flower extract (Rosa Damascena Mill) with a concentration of 75% and 100% can inhibit the growth of root canal bacteria